House prices, wealth effects and labour supply - Disney, Richard; Gathergood, John (Wiley, 2018)
We examine the impact of house prices on labour supply decisions using UK micro data. We combine household survey data with local level house price measures and controls for local labour demand. Our micro data also allows us to control for individual level income expectations. We find significant house price effects on labour supply, consistent with leisure being a normal good. Labour supply responses to house prices are concentrated among young married female owners and older owners. This finding suggests house prices affect the decisions of marginal workers in the economy. Our estimates imply house prices are economically important for the participation decisions for these workers.